(untitled) (European Journal of Education, 2022)
In this article a closer look will be taken on motivation, expectation, and present situation of third year undergraduate students of German studies in Croatia at the University of Rijeka. Due to the author’s extensive experience in teaching translation classes from Croatian to German for undergraduate students in the third year, it is noticeable that most students have problems in certain areas, i.e. they are not able to correctly translate short Croatian texts into German in terms of correct grammar and syntax, even when words were explained in advance to facilitate the process of translation and upon extensive grammar practice in the first and second year of undergraduate studies. As studying a language also requires a lot of self-study and interest in the language being studied, it is certainly not enough just to sit in the courses at the university and do only the most necessary things to somehow pass the exams. It is essential to be engaged intensively with the country, the culture, and the people, to take part in exchange programmes, travel as often as possible to the country whose language you are about to learn, take the opportunity to communicate with native speakers, watch films or TV shows, read books or magazines in the target language etc. Thanks to the new technologies, nowadays one has almost endless possibilities to be exposed to the target language, even if one does not have the opportunity to travel to the destination country. But to what extent do students use what is available to them and are they at all motivated for the necessary effort of self-study? To answer these questions, a questionnaire was prepared to gain a deeper insight into the students’ motivation to enrol German language and literature at the university, their expectations of what the language study would be like and the present situation in their third year of undergraduate studies. The evaluation of the questionnaire should provide information on the extent to which the students were familiar with what to expect from their studies, how they deal with the requirements and challenges, to what extent they are willing and prepared to do something outside of the courses to improve their language proficiency autonomously, what the study of German studies should serve them in the future and if self-study has a visible impact on their language proficiency, i.e. if students who do a certain amount of self-study do have better results.